2005
DOI: 10.1002/jobm.200410548
|View full text |Cite
|
Sign up to set email alerts
|

Sequential parametric optimization of lipase production by a mutant strain Rhizopus sp. BTNT‐2

Abstract: Lipase production by the mutant strain Rhizopus sp. BTNT-2 was optimized in submerged fermentation. Different chemical and physical parameters such as carbon sources, nitrogen sources, oils, inoculum level, pH, incubation time, incubation temperature and aeration have been extensively studied to increase lipase productivity. Potato starch (1.25% w/v) as a carbon source, corn steep liquor (1.5% w/v) as a nitrogen source and olive oil (0.5% v/v) as lipid source were found to be optimal for lipase production. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Similar effects were reported on lipase production in Rhizopus sp. BTNT-2 [3] and Yarrowia lipolytica [13]. In contrast, the addition of surfactant to the culture medium has been shown to increase the secretion of lipolytic enzymes in a number of microorganisms, attributable to alteration of cell permeability leading to increased protein secretion or to surface effects on cell-bound enzymes [39].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Similar effects were reported on lipase production in Rhizopus sp. BTNT-2 [3] and Yarrowia lipolytica [13]. In contrast, the addition of surfactant to the culture medium has been shown to increase the secretion of lipolytic enzymes in a number of microorganisms, attributable to alteration of cell permeability leading to increased protein secretion or to surface effects on cell-bound enzymes [39].…”
Section: Discussionmentioning
confidence: 93%
“…Actinomycete strains were grown on GYM agar slants (g/l: glucose 4.0 g; yeast extract 4.0 g; malt extract 10 g; CaCO 3 2.0 g; agar 12.0 g; pH 7.2). The working stock cultures were maintained and stored on GYM slants at 4°C.…”
Section: Maintenance Of Microorganismsmentioning
confidence: 99%
“…This study was also supported by the positive effect of olive oil, tributyrin, coconut oil and castor oil on lipase production by Rhizopus sp. BTNT-2 (Bapiraju et al 2005). In the present study, the effect of different concentrations of cod liver oil on lipase production showed a positive linear increase (11.2-15.53 U/ml) as the concentration of cod liver oil increased from 0.5 to 1.5%.…”
Section: Effect Of Various Triglycerides On Lipase Productionmentioning
confidence: 97%
“…In contrast, the addition of vegetable oils (olive, corn, and soybean oil) did not significantly affect lipase production. Bapiraju et al (2005) optimized the lipase production by the mutant strain Rhizopus sp. BTNT-2 in SmF.…”
Section: Agroindustrial Residuesmentioning
confidence: 99%
“…Bapiraju et al (2005) optimized the lipase production by the mutant strain of Rhizopus sp. and the optimum activity was 29 U mL −1 .…”
Section: Filamentous Fungimentioning
confidence: 99%